Spaced Education Improves the Retention of Laparoscopic Suturing Skills: A Randomized Controlled Study - Boettcher, Johannes; Klippgen, Lea; Mietzsch, Stefan; Grube, Friederike; Krebs, Thomas; Bergholz, Robert; Reinshagen, Konrad; Boettcher, Michael (European Journal of Pediatric Surgery, 2020)
Introduction Spaced learning has been shown to be superior in complex motor skill acquisition like laparoscopic suturing and knot tying. By using a pre–post follow-up design, the aim of the study was to evaluate the long-term impact of implementation of the spaced learning concept in laparoscopic training.Materials and Methods To evaluate the effectiveness of spaced learning, subjects were asked to perform four surgeon's square knots on a bowel model within 30 minutes—prior and after 3 hours of hands-on training. To examine the long-term skills, the same students were asked to perform a comparable, but more complex, task (four slip knots in a model of esophageal atresia) 12 months later as follow-up measurement. Total time, knot stability (evaluated via tensiometer), suture accuracy, knot quality (Muresan scale), and laparoscopic performance (Munz checklist) were assessed. Moreover, motivation was accessed using Questionnaire on Current Motivation.Results Twenty students were included in the study; after simple randomization, 10 were trained using the “spaced learning” concept and 10 via traditional methods. Both groups had comparable baseline characteristics and improved after training significantly, regarding all aspects assessed in this study. Subjects that trained via spaced learning were superior in terms of speed (p = 0.021), knot quality (p = 0.008), and suture strength (p = 0.003). Additionally, spaced learning significantly decreased anxiety (p = 0.029) and probability of success (p = 0.005).Conclusion The spaced learning concept is very suitable for long-term complex motor skill acquisition, like laparoscopic suturing and knot tying. It is superior to conventional training regarding speed and, most importantly, knot quality and stability, resulting in improved confidence and motivation. Thus, we strongly recommend to incorporate the spaced learning concept into training courses and surgical programs.
Keywords: laparoscopy; training; spaced learning